PENGARUH LAMA PENYIMPANAN TERHADAP DAYA SUKA SENSORI DAGING BROILER YANG DIBERI EKSTRAK BAWANG PUTIH SEBAGAI PENGAWET - Aprinando, Riyanti, dan Dian Septinova (Jurnal Riset dan Inovasi Peternakan (Journal of Research and Innovation of Animals), 2019)
Garlic (Alliumsativum Linn) is one of the herbs that have been shown to inhibit the growth of microorganisms. Component of garlic that has been shown to inhibit microbe is allicin or diallyl acid tiosulfinat. This study aims to determine the effect of storage length on preference test sensory color, aroma, flavor chunks of breast meat of broilers fed extracts of garlic, Determine the effect of storage length to the preference test sensory color, aroma, and flavor chunks of breast meat of broilers fed extracts of garlic. This research was conducted at the Laboratory of Animal Production and Reproduction Department of Animal Husbandry, Faculty of Agriculture, University of Lampung and meat samples obtained from RPA Hi. Nasir, Jl. Skin,Langkapura, Kemiling, Bandar Lampung City. Treatment using a completely randomized design (CRD) with four treatments and twenty replications. The treatments were storage length 0, 3, 6, 9 hoursmeat broiler fed extracts of garlic. The data were analyzed ANOVA(Analysis of Variance) at the 5% significance level.These results indicate that giving garlic extract 10% inmeat storage broiler 0, 3, 6, 9 hours no real effect (P> 0.05) to power the likes sensory (color, aroma, and flavor). Keywords: meat broiler, garlic, storage length, preference test, sensory.